Преимагинальные фазы развития и экология ольхового фиолетового листоеда - Бровдий, В.М. (Вестник зоологии, 1968)
Agelastica alni L. causes main damages to Alnus glutinosa Gaertn. in the Ukraine. It is also registered as a pest on birch-tree, willow and hazel-nut. The wintering beetles appear in the Central Forest Steppe and Polesye of the Ukraine in the third decade of April, when the temperature of the air is above 14° C. Mating and oviposition take place during May and the first decade of June. The female produces 400-550 eggs. The first larvae appear in the third decade of May. They develop on the leaves of plants for one month. Pupae develop in soil for 8-12 days. Young beetles ap-pear on plants at the end of June — beginning of July and only in August or first decade of September they go for wintering. Under conditions of the Ukraine only one genera-tion develops per year. Alnus glutinosa Gaertn. infection with Agelastica alni L. reaches 80%. Beetles and larvae in the places of their reproduction eat about 45% of leaf surface of this plant per year and often completely eat the leaves of the trees. The morphological characteristip of the egg, larva and pupa of Agelastica alai L. is given in the article.